829 Tumor alpha-fetoprotein inhibits cholesterol and steroid metabolism in monocyte-derived dendritic cells. (9th November 2020) - Munson, Paul; Adamik, Juraj; Butterfield, Lisa
Abstract : Background: Hepatocellular carcinoma (HCC) is a particularly lethal malignancy in part due to the potently immune-suppressive tumor microenvironment. The weak immune response is due in part to the presence of tumor alpha-fetoprotein (tAFP), a fetal glycoprotein that is produced by a majority of HCC tumors. 1 Previously, we showed that tAFP potently inhibited the differentiation of monocytes to dendritic cells when compared to cord blood-derived normal AFP (nAFP) and ovalbumin (OVA). 2 Additionally, we demonstrated that tAFP inhibits lipid metabolism by limiting the expression of fatty acid metabolic enzymes. 3 To identify the mechanism whereby tAFP alters dendritic cell metabolism, we analyzed microarray data by a functional enrichment pathway analysis with g: Profiler. 4 Methods: Monocytes from healthy donors (n=4) were isolated with CD14 magnetic beads and differentiated for five days in the presence of IL-4 and GM-CSF with OVA, nAFP, or tAFP. After five days, we isolated RNA for microarray analysis using an Affymetrix HG-U133A array. R studio generated principal component analysis. Differentially expressed (DE) genes were identified as a 1 log fold change and had adjusted p values of Results: Principal component analysis of the gene expression data revealed that tAFP clustered separately from OVA and nAFP based on PC1 (p = 0.016) and PC2 (p = 0.009) (figure 1). In total, 688 DE genes were identified with 495 upregulated and 193 downregulated (figure 2). Downregulated DE genes between tAFP versus nAFP yielded significantly down regulated pathways including cholesterol (p = 10e-7.5), steroid (p = 10e-7.5), and lipid biosynthesis (p = 10e-6) (figure 3). Interestingly, upregulated DE genes between tAFP versus nAFP included many pathways specific to stress response to metal ions including zinc (p = 10e-10.5) and copper (p = 10e-10) (figure 4). Conclusions: In addition to validating previous data demonstrating tAFP inhibited lipid biosynthesis generally, this is the first report to our knowledge of tAFP inhibiting gene signatures associated with cholesterol and sterol synthesis specifically. Furthermore, we identified significant upregulation of gene pathways corresponding to the stress response genes to metal ions. Notably, functional assays are underway to confirm these gene pathway data. These findings shed new insight into how tAFP perturbs monocyte and DC metabolism and thereby limits differentiation of monocytes to immature dendritic cells. Future insights into how tAFP limits innate immunity could lead to improved immunotherapies for HCC. Ethics Approval: Samples were collected with informed consent at the University of Pittsburgh (Pitt IRB #UPCI 04-001 and UPCI 04-111). References: Chan SL, Mo FKF, Johnson PJ, Hui EP, Ma BBY, Ho WM, et al. New utility of an old marker: serial alpha-fetoprotein measurement in predicting radiologic response and survival of patients with hepatocellular carcinoma undergoing systemic chemotherapy. J Clin Oncol Off J Am Soc Clin Oncol 2009;27:446–52. https://doi.org/10.1200/JCO.2008.18.8151 Pardee AD, Shi J, Butterfield LH. Tumor-derived α-fetoprotein impairs the differentiation and T cell stimulatory activity of human dendritic cells. J Immunol 2014;193:5723–32. https://doi.org/10.4049/jimmunol.1400725 Santos PM, Menk AV, Shi J, Tsung A, Delgoffe GM, Butterfield LH. Tumor-derived α-fetoprotein suppresses fatty acid metabolism and oxidative phosphorylation in dendritic cells. Cancer Immunol Res 2019;7:1001–12. https://doi.org/10.1158/2326-6066.cir-18-0513 Raudvere U, Kolberg L, Kuzmin I, Arak T, Adler P, Peterson H, et al. g:Profiler: a web server for functional enrichment analysis and conversions of gene lists (2019 update). Nucleic Acids Res 2019;47:W191–8. https://doi.org/10.1093/nar/gkz369